A Canadian national survey of attitudes and knowledge regarding preventive vaccines - Ritvo, Paul (BioMed Central, 2003)
BACKGROUND: Vaccines have virtually eliminated many diseases, but public concerns about their safety could undermine future public health initiatives. OBJECTIVE: To determine Canadians' attitudes and knowledge about vaccines, particularly in view of increasing public concern about bioterrorism and the possible need for emergency immunizations after weaponized anthrax incidents and the events of September 11, 2001. METHOD: A 20-question survey based on well-researched dimensions of vaccine responsiveness was telephone-administered to a random sample of N = 1330 adult Canadians in January, 2002. RESULTS: 1057 (79.5%) completed the survey. Respondents perceived vaccines to be highly effective and demonstrated considerable support for further vaccine research. However, results also indicate a lack of knowledge about vaccines and uncertainty regarding the safety. CONCLUSIONS: Support for vaccines is broad but shallow. While Canadians hold generally positive attitudes about vaccines, support could be undermined by widely publicized adverse events. Better public education is required to maintain support for future public health initiatives.